2005
DOI: 10.1080/00071660500065359
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial eggshell contamination in conventional cages, furnished cages and aviary housing systems for laying hens

Abstract: The influence of housing system on the initial bacterial contamination of the eggshell was studied. Two long-term experiments were performed. Bacterial eggshell contamination, as expressed by total count of aerobic and Gram-negative bacteria, was periodically analysed for eggs from a conventional cage, a furnished cage with nest boxes containing artificial turf or grids as nest-floor material and an aviary housing system. Results were log-transformed prior to statistical analyses. For both experiments no syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 15 publications
5
74
0
6
Order By: Relevance
“…In the study, the significantly lower value of this feature (up to day 8 of embryogenesis) in eggs laid by females reared in cages can be associated with a lower microbial contamination of these eggs. In fact, the results of the experiment conducted by De Reu et al (2005) confirm this statement. They reported a lower egg contamination (aerobic bacteria) of laying hens when birds were kept in cages instead of aviaries.…”
Section: Discussionsupporting
confidence: 77%
“…In the study, the significantly lower value of this feature (up to day 8 of embryogenesis) in eggs laid by females reared in cages can be associated with a lower microbial contamination of these eggs. In fact, the results of the experiment conducted by De Reu et al (2005) confirm this statement. They reported a lower egg contamination (aerobic bacteria) of laying hens when birds were kept in cages instead of aviaries.…”
Section: Discussionsupporting
confidence: 77%
“…The highest microorganism count in the litter was determined at the late rearing period of birds (Witkowska et al, 2010). De Reu et al (2005, however, estimated that air in the poultry house with a deep litter floor system had approximately nine times more bacteria than air in the facility with a cage system.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effect of time and temperature on the development of rots, it is generally recognized that the longer the exposure of eggs to bacteria and the greater the contamination of eggshells, the higher the penetration rate (Javed et al, 1994;Chen et al, 1996;Miyamoto et al, 1998;Messens et al, 2006;Messens et al, 2007;Al-Bahry et al, 2012). The level of eggshell contamination is also recognized as depending on the season: lower counts are observed in winter, corresponding to low environmental temperatures, for the total aerobic flora and gram-negative bacteria (De Reu et al, 2005), for the total aerobic bacteria and Enterococcus (Mallet et al, 2006) and for the B. cereus group (Koné et al, 2013). Quarles et al (1970) also suggested that high temperatures might lead to higher levels of eggshell contaminants.…”
Section: Effects Of Temperature and Time On Spoilage Bacteriamentioning
confidence: 99%
“…The level of bacteria present on the eggshell surface ranges between 3.8 and 6.3 log CFU/egg depending on the study, with an average value of 4.5 log CFU/egg (Moats, 1981;Lucore et al, 1997;Favier et al, 2000;Jones et al, 2004;De Reu et al, 2005;Musgrove et al, 2005a;De Reu et al, 2006b). The gram-positive flora is dominant at the surface, comprising the genera Micrococcus, Staphylococcus, Streptococcus, Aerococcus and, to a lesser extent, Bacillus (Moats, 1979;De Reu et al, 2006b).…”
Section: Effects Of Temperature and Time On Spoilage Bacteriamentioning
confidence: 99%